Cycloartane triterpenes from Euphorbia tuckeyana - Ferreira, MJU (2015)
Investigation of the acetone extract of the whole plant of Euphorbia tuckeyana afforded a new cycloartane-type triterpene named as cyclotucanol. Its structure was established as cycloartane-24-methylene-3beta,25-diol (1). The known cycloartane triterpenes cycloeucalenol (2), 3,8-hydroxy-cycloart-25-en-24-one (3), cycloart-25-ene-3beta,24-diol (4), 25,26,27-trisnor-3beta-hydroxycycloartan-24-al (5) and cycloart-23-ene-3beta,25-diol (6) were also isolated and identified.